Social car: The research of interaction design on the driver's communication system. (17th January 2019) - Yu, Zhao; Lin, Xun
Summary: Road traffic in the city is changing with each passing day. The current communication system is based on sound, light, and other ways. Insufficient information may lead to misunderstandings and conflicts among drivers. We hope to use the existing digital information and interaction technology in designing socialized information service for automobiles. This is to enable drivers to exercise a more social behavior while driving. In this paper, the interaction design of a driver communication system is studied. We carried out three driving simulation experiments to study three different ways of interaction interfaces and then promoted a questionnaire based on NASA TLX to understand the subjective feelings and subjective workload of drivers in using these interaction interfaces. The four dimensions of driving quality evaluation, road attention evaluation, interaction effect evaluation, and subjective evaluation are analyzed. The results suggest four ideas. (a) The distractions of the audio and text interface are far below that of the video interface. The audio interface has the least distraction by sending information. (b) The errors in words or pronunciation barely affect the understanding of the meaning of the drivers' message. However, it will cause an increase in distraction. (c) Marking some important information in text display gives drivers a better understanding and interaction experience. (d) The video interface gives drivers a sense of social participation. According to these conclusions, we can give some guidance to the driver's communication system. It not only helps the drivers accomplish the driving task but also creates more social actions with other drivers. It is necessary to reduce driving distraction and enhance the availability for the communication system in the future.